2014
DOI: 10.14419/ijbas.v3i3.2927
|View full text |Cite
|
Sign up to set email alerts
|

Effect of processing methods on the proximate composition of African yam bean (Sphenostylis stenocarpa) flours and sensory characteristics of their gruels

Abstract: Background: African yam bean (AYB) could be processed into value added food products. Processing however affects the chemical, sensory and functional properties of the foods. Objectives: This work determined the effect of processing methods on the proximate composition of African yam bean (Sphenostylis stenocarpa) flour and the sensory properties of its gruels. Methods: Six kilogram of African yam bean seeds were sorted and divided into 4 portions of 1.5kg each. One portion was washed and fermented without lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Raw AYB had the least protein value (20%). The significant increase observed in the protein content of the flours especially dehulled AYB fermented for 24 h in 0.5% citric acid medium is not surprising as studies have indicated an increase in the protein contents of fermented foods [26,27]. The result can also be attributed to the citric acid used; fermentation in citric acid medium have been shown to significantly increase the protein contents of foods, this increase can be attributed to the low pH provided by the citric acid thereby facilitating protein solubilization, resulting in higher protein yields [28,29].…”
Section: Effect Of Varying Fermentation Time On the Proximate Composition Of Whole And Dehulled Ayb Flours Fermented In 05% Citric Acid Smentioning
confidence: 80%
“…Raw AYB had the least protein value (20%). The significant increase observed in the protein content of the flours especially dehulled AYB fermented for 24 h in 0.5% citric acid medium is not surprising as studies have indicated an increase in the protein contents of fermented foods [26,27]. The result can also be attributed to the citric acid used; fermentation in citric acid medium have been shown to significantly increase the protein contents of foods, this increase can be attributed to the low pH provided by the citric acid thereby facilitating protein solubilization, resulting in higher protein yields [28,29].…”
Section: Effect Of Varying Fermentation Time On the Proximate Composition Of Whole And Dehulled Ayb Flours Fermented In 05% Citric Acid Smentioning
confidence: 80%
“…These were done for a period of four (4) months. Effect of processing on nutritional composition of AYB was sourced from the reports of Abioye et al (2015), Adewale et al (2013), and Ngwu et al (2014). This spanned for a period of one (1) month.…”
Section: Methodsmentioning
confidence: 99%
“…It was revealed that the nutritional composition of AYB consists of carbohydrate (63.39), ash (3.41), fat (0.54), protein (20.37) and crude fiber (1.54). The average mineral composition comprised Na (496), K (620), Ca (92), Mg (103), P (251), Zn (6), Fe (53), Mn (12), Cu (1.3), Cd (2.1) but Hg, As, Ni were found below detection limit (Abioye et al, 2015;Adewale et al, 2013;Ajayi et al, 2010;Ngwu et al, 2014). Yusufu et al (2013) evaluated complementary food produced from sorghum, AYB and mango mesocarp flour blends and reported an increase in the protein and fat level of the formulated complementary food from 8.90 to 17.40 and 1.50 to 3.50, respectively.…”
Section: Nutritional Composition Of Aybmentioning
confidence: 99%
“…Aside the condiment used, the method of preparation of the soups which differed from methods 3 and 4 by toasting of the groundnut before milling could also have contributed to the acceptability statue of the soup. Toasting or roasting as a method of cooking is well known to improve flavour and food acceptability [19]. Aside the method of preparation and the use of 'dadawa' as the food condiment, the variant vegetables might have influenced the acceptability statues of the soups.…”
Section: Sensory Evaluation Of Egusi Soupmentioning
confidence: 99%